Exercise-induced changes in muscle size do not contribute to exercise-induced changes in muscle strength - Loenneke, J. P.; Buckner, S. L.; Dankel, S. J.; Abe, T. (Sports Medicine, 2019)
Early work from Ikai and Fukunaga [1] found that those with smaller muscle cross-sectional areas had less arm strength than those with larger muscle cross-sectional areas. However, the question that remains is whether the exercise-induced change in muscle size contributes to the exercise-induced change in muscle strength. The current model for explaining changes in muscle strength is that neural mechanisms play a role initially followed by larger contributions from muscle hypertrophy.